Eye Lethargy Sleepiness Detection Based on Driver’s Experience Using Image Mining - et. al., Stephen raj. S, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The retina part of the eye is been taken as the detection part in our work. Thus, it could involve three set of parameter to avoid the accident. There are only the persons who having the age limit of 20 ages, if the person who is below this age means there are prohibited to drive. And the second one is that if the person who is owning the car is also want to make a decision whether there are in the alter stage/drowsy. If there are in the drowsy state/fatigue there are not permitted to drive.The third case, is that if the owners and drivers are having the relationship in the form of the call taxi services means they must be a reliable behavior must be approved in connecting among themselves. In order to make a satisfactory of the owner the driver who is allotted for the driving, they have to detect the person state of mind by seeing this eye and monitor them for the further detection of the safe driving. Thus the image is been captured from web camera and it will be having the database of the saved images of the person who are been detected already. Now the new person who are been detected to check the drowsiness they are been checked with the database and export the result in the acquired time.